MIL-101(Fe) nanodot-induced improvement of adsorption and photocatalytic activity of carbon fiber/TiO2-based weavable photocatalyst for removing pharmaceutical pollutants. (25th March 2021) - Zhang, Yan; Xiong, Meiyu; Sun, Anran; Shi, Zhun; Zhu, Bo; Macharia, Daniel K.; Li, Fang; Chen, Zhigang; Liu, Jianshe; Zhang, Lisha
Abstract: The decoration of TiO2 -based junctions on carbon fibers (CFs) has been well-developed as weavable photocatalysts for degrading hazardous pharmaceutical pollutants, but their practical application is still constrained by unsatisfactory adsorption and photodegradation performances, resulting from low surface area/porosity and photoactivity. Herein, we propose the growth of MIL-101(Fe) nanodots with small size of 5–10 nm as a porous co-photocatalyst to decorate TiO2 nanorods on CFs. CFs/TiO2 /MIL-101(Fe) bundles display a wide absorption with an edge (∼600 nm). Subsequently, CFs/TiO2 /MIL-101(Fe) bundles are weaved into a macroscopical cloth (0.2 g, 4 × 4 cm 2 ). CFs/TiO2 /MIL-101(Fe) cloth can efficiently adsorb 46.9% 17β-estradiol (E2) and 40.2% tetracycline hydrochloride (TC) after 60 min in the dark, with obvious improvement (5.4–8.4 times) compared with that by CFs/TiO2 cloth (8.7% E2 and 4.8% TC). Importantly, under visible light irradiation, CFs/TiO2 /MIL-101(Fe) cloth can remove 87.4% E2 and 94.2% TC in 60 min, which is 6–13.1 times compared with that by CFs/TiO2 cloth (14.6% E2 and 7.2% TC), resulting from the high adsorption and three-component synergistic photocatalytic activity. Therefore, the construction of semiconductor-MOF nanojunctions on CFs provides a general strategy to develop novel weavable photocatalysts for eliminating pharmaceutical pollutants. Graphical abstract: CFs/TiO2 /MIL-101(Fe) can be used as weavable photocatalyst to eliminate pharmaceutical pollutants in water. Image 1 Highlights: Successful decoration of TiO2 nanorods on CFs with MIL-101(Fe) nanodots. High adsorption ability due to large surface area and total pore volume. High photocatalytic activity owing to three-component synergistic effect. Good stability with a simple recycling process.